Hyers-Ulam-Rassias Stability for a First Order Functional Differential Equation - Tunç, Cemil; Biçer, Emel (Journal of Mathematical and Fundamental Sciences, 2015)
In this paper, by using the fixed point method, we prove two new results on the Hyers-Ulam-Rassias and the Hyers-Ulam stability for the first order delay differential equation of the form y"²(t) = F(t, y(t), y(t âˆ’Ï„ )). Our results improve some related results in the literature.